Upaya Peningkatan Keselamatan Pasien Di Rumah Sakit : Literature Review - Nur Akbar Adi Saputro; Endang Pertiwiwati; Ichsan Rizany (School of Nursing, Faculty of Medicine and Health Science, Lambung Mangkurat University., 2023)
Hospitals are obliged to fulfill the right of patients to obtain safety and security while in hospital care to avoid NearMiss (Near-injury Events /KNC) and Adversert Events (Unexpected Events / KTD). The high incidence of patientsafety incidents in this hospital is a concern, because it can injure patients so that it can cause death in patients.Efforts that can improve patient safety. This study was conducted with literature review. ten literatures were identifiedfrom four databases: